Primeiro relato de Aetalion reticulatum (L.) (Hemiptera: Aetalionidae) infestando plantas de noni [Morinda citrifolia L. (Rubiaceae)] - de Castro, Marcelo Tavares; Montalvão, Sandro Coelho Linhares (EntomoBrasilis, 2019)
Resumo. Aetalion reticulatum (L.) (Hemiptera: Aetalionidae), uma cigarrinha altamente polífaga e reconhecidamente praga de várias culturas agrícolas e florestais, é relatada pela primeira vez infestando plantas de noni, Morinda citrifolia L. (Gentianales: Rubiaceae), em Brasília, Distrito Federal, Brasil. Esse novo registro aumenta a lista de hospedeiras do inseto, reforçando a necessidade de estudos mais aprofundados sobre essa cigarrinha e o seu controle. First report of Aetalion reticulatum (L.) (Hemiptera: Aetalionidae) infesting plants of noni [Morinda citrifolia L. (Rubiaceae)] Abstract. Aetalion reticulatum (L.) (Hemiptera: Aetalionidae), a highly polyphagous leafhooper and known to be pest of various agricultural and forestry crops, is reported for the first-time infesting noni plants, Morinda citrifolia L. (Gentianales: Rubiaceae), in Brasília, Federal District, Brazil. This new record increases the host’s list of this insect, reinforcing the necessity for more in-depth studies of this leafhooper and its control.